GBA-Associated Synucleinopathies: Prime Candidates for Alpha-Synuclein Targeting Compounds - Brockmann, Kathrin (Frontiers in Cell and Developmental Biology, 2020)
As we are now entering the era where disease-modifying treatment options such as alpha-synuclein targeting compounds are tested in clinical trials, patient stratification according to alpha-synuclein-specific enrichment strategies are a much-needed prerequisite to introduce patients to specific therapies. Such a scenario will be exemplified for GBA, one major genetic risk factor that is specifically associated with the alpha-synucleinopathies Parkinson’s Disease and Dementia with Lewy Bodies.